PENDAMPINGAN PEMBUATAN FOTO UNTUK GURU SD KECAMATAN SUKAMAKMUR KABUPATEN BOGOR - Zuhdi HS; Nurdin Ibrahim; Cecep Kustandi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
The low student learning outcomes of SDN Sukamakmur Bogor District based on the analysis conducted because teachers still use the traditional approach, marked by still dominant activity while students are only as listeners and recipients of information. students only listen to the teacher's explanation and take notes or summarize the important things from the material presented. Therefore it is necessary to strive for the use of media and appropriate in the learning process, an interesting atmosphere so that students are more active in learning so that students' learning activities and outcomes increase. The approach applied to the Community Service Program is a model of empowerment through mentoring with the following steps: 1) Preparation Phase; 2) Assessment Phase; 3) Alternative Planning Phase of Programs or Activities; 4) Formulation Phase of the Action Plan; 5) Stage of Implementation (Implementation) of the Program or Activity; 6) Evaluation Phase; and 7) Termination Phase. This Community Service is carried out as an empowerment of elementary school teachers in the District of Sukamakmur, Bogor Regency, producing Photo Media that meets theoretically feasible criteria; meet the proper criteria in terms of format, content and appearance; have high applicability or are worthy of learning.